P53‐Mediated Repression of the Reprogramming in Cloned Bovine Embryos Through Direct Interaction with HDAC1 and Indirect Interaction with DNMT3A. Issue 3 (6th March 2015) - Ma, PJ; Zhang, H; Li, R; Wang, YS; Zhang, Y; Hua, S
Contents: P53 is a transcriptional activator, regulating growth arrest, DNA repair and apoptosis. We found that the expression level of P53 and the epigenetic profiles were significantly different in bovine somatic cell nuclear transfer embryos from those in vitro fertilization (IVF) embryos. So we inferred that abnormally expression of P53 might contribute to the incomplete reprogramming. Using bovine foetal fibroblasts, we constructed and screened a highly efficient shRNA vector targeting bovine P53 gene and then reconstituted somatic cell nuclear transfer embryos (RNAi‐SCNT). The results indicated that expression levels of P53 were downregulated significantly in RNAi‐SCNT embryos, and the blastulation rate and the total number of cell increased significantly. Moreover, methylation levels of CpG islands located 5′ region of OCT4, NANOG, H19 and IGF2R in RNAi ‐SCNT embryos were significantly normalized to that IVF embryos, and the methylation levels of genome DNA, H3K9 and H4K5 acetylation levels were also returned to levels similar to the IVF embryos. Differentially expressed genes were identified by microarray, and 28 transcripts were found to be significantly different (> twofolds) in RNAi‐SCNT embryos compared to the control nuclear transfer embryos (SCNT). Among the 28 differentially expressed transcripts, just HDAC1 and DNMT3A were closely associated with the epigenetic modifications. Finally, ChIP further showed that P53 might repress the epigenetic reprogramming by regulating HDAC1 directly and DNMT3A indirectly. These findings offer significant references to further elucidate the mechanism of epigenetic reprogramming in SCNT embryos.